2013
DOI: 10.4186/ej.2013.17.4.93
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Single Wall Carbon Nanotubes and Activated Carbon with Water Adsorption in Finite-Length Pore Models

Abstract: Abstract. Grand Canonical Monte Carlo simulation is used to study water adsorption in activated carbon (AC) and carbon nanotubes (CNT) which is modelled as a bundle of seven tubes, and the simulation results are compared with the experimental data. To investigate the role of functional groups on water adsorption, hydroxyl groups are grafted at various locations on the surface of AC and CNT. For carbon nanotubes, the spacing between tubes can affect the isotherm. For small spacing and functional groups are loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In a study of water adsorption in a more realistic f-CNT system, having a single hydroxyl group grafted at various locations of the exterior of the CNT, Wongkoblap et al [ 211 ] found with MD simulations that this change increases the adsorption of water molecules at the exterior of the CNT (in the space between CNT tubes in a bundle), but has very little effect on water uptake inside the tube. According to this study, the only discernible effect of the hydroxyl groups on internal water is that the onset of the uptake process happens at a lower pressure (below 0.5p ), than in pristine CNT tubes.…”
Section: Effect Of Cnt Impurities Defects and Functionalizationmentioning
confidence: 99%
“…In a study of water adsorption in a more realistic f-CNT system, having a single hydroxyl group grafted at various locations of the exterior of the CNT, Wongkoblap et al [ 211 ] found with MD simulations that this change increases the adsorption of water molecules at the exterior of the CNT (in the space between CNT tubes in a bundle), but has very little effect on water uptake inside the tube. According to this study, the only discernible effect of the hydroxyl groups on internal water is that the onset of the uptake process happens at a lower pressure (below 0.5p ), than in pristine CNT tubes.…”
Section: Effect Of Cnt Impurities Defects and Functionalizationmentioning
confidence: 99%